Operationalizing Inclusive Growth : Per-Percentile Diagnostics to Inform Redistribution Policies - Kireyev, Alexei (IMF Working Papers; Working Paper ;, 2020)
Inclusive growth, narrowly defined in this paper as growth that helps reduce inequality, is achieved if consumption of the poor increases faster than consumption of the rich. The paper presents a simple accounting framework for a per-percentile consumption diagnostics that could inform redistribution policies. The proposed framework is illustrated in application to Iraq and Tunisia.